Pengaruh Training Karyawan terhadap Kinerja Karyawan yang dimediasi oleh Produktivitas Kerja (Studi Kasus Karyawan PT. Berkah Subuh Transport) - Suraida, Herpina Hastara; Kiswoyo, Kiswoyo (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to examine the effect of employee training on employeeperformance mediated by work productivity. The method used is quantitative analysis by taking samples from employees working in the company. The results of the study indicate that the training variables reflected in the indicators of goals and objectives, trainers, methods, materials, training participants have a positive and significant effect on employee performance. Training activities carried out continuously by the company will improve employee abilities in carrying out their work which in turn can improve employee performance. Training variables described in indicators of goals and objectives, trainers, methods, materials, training participants have a positive and significant effect on employee performance through motivation. Training accompanied by motivation will have a significant impact which will ultimately affect employee performance.